Fostering Students’ Vocabulary Mastery Through K.I.M (Keyword, Information, And Memory Clue) Strategy at an Indonesian Junior Highschool Context - Assyarifullah Ramli; Rivaldin Rivaldin (Pascasarjana Universitas Negeri Makassar, 2021)
The objectives of this study were: “To find out the development of students' vocabulary mastery taught by the KIM method in class VIIA SMP N 3 Wundulako. Where the consequences of this study would be one of references material for English teachers or similar study in an effort to develop the students vocabulary. In this situation, Classroom Action Research (CAR) which became the research design was applied by the researcher. Researchers collaborated with English instructor at SMP Negeri 3 Wundulako. The samples of this study were 15 students of class VIIA. Data collection was done by means of tests that are prepared in the form of multiple choices and also observation sheets to measure the level of success or achievement of learning objectives in teaching and learning activities in class. This research was conducted in two cycles where the first cycle showed that only six students achieved the KKM score. And nine students with an average value of 56 with a success percentage of only 40%. While in the second cycle there was an increase in 13 students achieving the KKM score with an average value of 83 with a percentage of 86%. Which proved that by using vocabulary teaching strategies using KIM (keyword information and memory clue) strategies can improve students' vocabulary skills.